Get the "unknown" (in this case y) by itself on one side of the equation. Here, you might start by getting both "y"s on the left and anything not involving "y" on the right. Since there is a "y/2" added on the left, do the opposite: subtract y/2 from both sides: 3y+ 4- y/2= y/2+ 9- y/2 becomes (3- 1/2)y+ 4= 9 or (6/2- 1/2)y+ 4= (5/2)y+ 4= 9. Now subtract 4 from both sides: (5/2)y+ 4- 4= 9- 4 or (5/2)y= 5. Since y is nowmultipliedby 5/2, do the opposite: divide both sides by 5/2 (or, same thing, multiply both sides by 2/5): (2/5)(5/2)y= (2/5)(5) or y= 2.